Water Cunsumption and Nutrient Uptake by Eucalypts - Tiwari, K. M.; Mathur, R. S. (Indian Forester, 1983)
In the context of raising large scale plantations of Euocalyptus species to meet the increasing demands of the society for firewood, timber. Poles, pulpwood and oil etc, there is a general belief that Eucalyptus tree consumes more water and soil nutrients. In the present paper information on water and nutrient relation. Of Eucalyptus species has been highlighted. It is seen that the present fallacy that Eucalyptus lowers the underground water table of the soil is not borne out by scientific investigation.